Selective adsorption from polymer mixtures on solid surfaces - Vakarin, E.V.; Holovko, M.F. (Condensed Matter Physics, 2001)
Selective adsorption from binary polymer mixtures on a crystalline surface
is studied in terms of the lattice gas model in conjunction with the results
of the association theory. An interplay of the selectivity and the surface
induced segregation is shown to result in a variety of competing factors
which dominate the adsorption process. The role of the bead diameter,
chain length and the surface activity in the preferential adsorption of one
component is analyzed. A variation of the selectivity coefficient with the
density and composition is also discussed. Селективна адсорбція з бінарної полімерної суміші на кристалічній
поверхні вивчається в рамках моделі граткового газу в комбінації з
результатами асоціативної теорії. Показано, що взаємовплив селективності та поверхнево-індукованої сегрегації приводить до різно-
манітних конкуруючих факторів, що визначають процес адсорбції.
Проаналізовано роль діаметра сегмента, довжини ланцюга та поверхневої активності у переважній адсорбції одної компоненти. Обговорюється також зміна коефіцієнта селективності з густиною та концентраційним складом.